Influence of garden cress seeds supplementation on immunity, hormonal status, and milk quality during the last third of pregnancy and lactation period of rabbit does - Yassmine M. El-Gindy; Soliman M. Zahran; Mohamed H. Ahmed; Azza Y. Idres; Sabrin A. Morshady (BMC Veterinary Research)
Abstract During the last third of pregnancy period, rabbits are exposed to many challenges, such as health complications and oxidative stress. The present study aims to use garden cress seeds (GAC) as a natural antioxidant to mitigate these challenges and evaluate its effects on reproductive performance, immunity, hormones, protein profile and milk quality. A total of 24 pregnant V-Line rabbits (pregnant at 20 days proved by palpation), with an initial body weight of 2395.83 g and about 6–7 months of age, were randomly distributed to 4 groups, the control group was fed the basal diet without GAC, the other treated groups GAC 3, GAC 4.5 and GAC 6 were fed the basal diet supplemented with 3, 4.5, and 6% GAC, respectively. The experiment lasted six weeks. The results revealed that treated female rabbits with different levels of GAC did not have a noticeable effect on milk yield, average daily milk yield, or most of the milk analysis parameters (milk density, total solids, solids not fat, lactose, ash, and protein). On the other hand, GAC showed a significant increase in milk fat, and GAC 3% rabbits displayed a higher percentage of milk fat (p < 0.050) than the other groups. Likewise, treatment with GAC also had a significant impact on serum total protein, globulin, IgG, and IgM. The 3% GAC rabbits showed significantly higher total protein, globulin, and IgM values than the control group. However, all GAC treatments significantly improved serum IgG and the best value was found in the 3% GAC group. In conclusion, our results demonstrated that feeding lactating rabbits a diet supplemented with GAC could be considered a good strategy to enhance immunity, protein profile, MY and milk fat. The best results were obtained with the GAC 3% treatment.